Om beters wille Rederijkerskamers en de stedelijke cultuur in de Zuidelijke Nederlanden (1400-1650) - van Bruaene, Anne-Laure (Amsterdam University Press, 2008)
In the 15th and 16th century a special institute developed in Flanders and Brabant: the chamber of rhetoric. Regular citizens started theater and lyricks, in small closed groups and in public. This study gives an overview of 227 chambers of rhetoric, the rhetorical culture in the Southern Netherlands and gives a fresh new look on the cultural history of the Netherlands.